The End of the Good Life: Literary Representations of Suburbia and the American Nightmare (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2015)
Conventional literary and filmic representations of the American suburbs depict a space that is either middle-class idyll or claustrophobic vacuum. By engaging with suburban gothic literature, this article interrogates such portrayals and deconstructs the utopian conception of suburbia. I argue that, rather than representing the "good life", the suburbs in these texts are sites of deeply-rooted cultural anxieties.